Treatment-resistant hypertension - Milošević, Maja; Otašević, Petar (Archives of Pharmacy, 2022)
Treatment-resistant hypertension is one of the most significant causes of poor blood pressure regulation. Patients with resistant hypertension are at a higher risk of developing comorbidities compared to the general hypertensive population. As a result, these patients have an increased incidence of disability and premature death, as well as increased treatment costs. Due to the above-mentioned, in the last decade, there has been an increase in researchers’ interest in elucidating the pathogenesis, diagnosis, and treatment of resistant hypertension. However, recent data indicate that 20% of female and 24% of male patients with arterial hypertension still have uncontrolled blood pressure, despite maximum doses of three antihypertensive drugs (including a diuretic) and appropriate lifestyle measures. New treatment modalities (i.e. device-based interventions - catheter-based renal denervation and baroreceptor stimulation) offer hope for achieving adequate blood pressure regulation in these patients. In this paper, we have summarized previous knowledge about the mechanisms underlying the pathogenesis of resistant hypertension, as well as optimal diagnostic methods to differentiate true from pseudo-resistant hypertension. We have also given an overview of the current therapeutic approach, including optimal medical therapy and new treatment modalities (i.e. device-based interventions) and their role in the treatment of resistant hypertension.